Sirenomelia- A rare congenital anomaly: Case report - Dipanjali Thombare; Prachi Dixit; Ankit Chavan; Ashwini Najan (Wolters Kluwer Medknow Publications, 2023)
Sirenomelia is an extremely uncommon congenital deformity in which neonate has fused lower limbs associated with various visceral malformations including urogenital and gastrointestinal tract, pulmonary hypoplasia, and potter's facies. The prevalence is 0.8 to 1 per 100,000 newborns. About 300 cases were recorded till date. We describe a case of 31-year G4P1L1A2 with previous lower segment caesarean section with gestational age of 22 weeks 5 days with anomaly scan suggestive of single live intrauterine pregnancy of 21 weeks 5 days with bilateral renal agenesis with placenta previa and no demonstrable amniotic fluid pocket seen. Her pregnancy was uneventful without any medical disorder, drug history, and no congenital anomaly in the family. Termination of pregnancy done by emergency hysterotomy and delivered anomalous foetus with fused lower limb with absent toes, low set ears, absent left ear ostium, imperforate anus, and absent external genitalia. Sirenomelia is fatal congenital anomaly with unclear etiology. Early antenatal diagnosis and termination of pregnancy is the treatment.